Effectiveness of Moist Heat Application on Elderly Orthopedic Clients at Selected Urban Community Area, Bengaluru - Princy P. (International Journal of Orthopedic Nursing and Practices, 2025)
Pain is a distressing sensory and emotional experience that arises from actual or potential tissue damage. It is a multifaceted phenomenon that extends beyond physical discomfort, encompassing emotional and psychological aspects as well. Individuals who recognize that pain management not only enhances comfort but also accelerates the healing process are more inclined to seek or administer appropriate treatment. In order to educate the elderly orthopedic clients, this study was conducted to assess the effectiveness of moist heat application on elderly orthopedic clients at selected urban community area, Bengaluru. A pre-experimental design, with non-probability convenient sampling method was used. Information was collected from 50 elderly orthopedic clients at selected urban community area, using the numerical pain rating scale. Majority (41.7%) of respondentsbelongs to the age group of 65–70 years, 58% of respondents were females, 68% were Hindus, 65% of respondents were married, 34% of respondents were not having formal education, 48% of subjects were retired and not working, 54% of respondents had monthly income of Rs. 5,001–10.000, and 58% of respondents had associated illnesses like hypertension, diabetes mellitus and other chronic disorders. The respondents had a pre-test mean score of 4.46 with a standard deviation of 1.06. In contrast, the post-test results showed a mean score of 2.29 and a standard deviation of 0.08. The pooled standard deviation of post-test and pre-test is 0.05, independent ‘t’ value is 15.14, df is 23 and probability of ‘t’ is 2.07. Since the independent ‘t’ value is greater than the probability of ‘t’, the application of moist heat is effective for the reduction of pain among elderly orthopedic clients and thus the hypothesis is accepted. Analysis of the study showed that there is no significant association between pain scale rate and socio-demographic variables such as age, gender, education status, family income and associated illness. The level of significance is at 5% level (P<0.05).
Keywords: Assess; Orthopedic; Pain; effectiveness; elderly clients; moist heat application